Cultural factors and senior tourism: Evidence from the Chinese context - Tuo, Jinmei; Deng, Renli; Tao, Ming; Xu, Zucai; Peng, Yan; Linghu, Yushuang; Huang, Shiming; Yu, Changyin (Frontiers in Psychology, 2022)
With the progressive aging of society, older people will increasingly participate in tourism, leading to great potential and prospects within the older population tourism market. However, there are many factors affecting older population tourism, including personal, cultural, social, and policy factors. Additionally, there are still many deficiencies in older population tourism. The present study aims to systematically summarise the current situation and factors influencing tourism in the older population, confirm motivations that affect participation in tourism activities among older people, and advance feasible suggestions for standardisation of the older population tourism market. The results can provide a reference for the development and implementation of older population tourism.